Analisis kriteria desain jalur pedestrian kawasan stasiun kereta api Padalarang - Alfred Wijaya; Sally Octaviana Sari (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Analysis of pedestrian design criteria of Padalarang railway station area The Padalarang sub urban is currently known as high mobility area. There are railway station and terminal for public transportation. Recently, Padalarang has decreasing its physical and visual quality due to the growth of informal housing, informal sector, traditional market and terminal. The Transit Oriented Development is an approach which integrates vehicle network system and pedestrian lane modes. These inappropriate growths generate a lot of environment problems. One of them is the lack of pedestrian lane and its linkage with housing, such as markets, stations, terminals and other public facilities, meanwhile pedestrian lanes have an important role for supporting their main activity. Especially pedestrian lanes in Indonesia which recently are still in ongoing debate as an important issue in town planning. This research will deliberate about the design criteria of pedestrian lane system become more walkable and responsive, which oriented to sidewalk users. This research was conducted through case study and data collecting by surveying, observing and mapping the physical condition of the area nearby railway station, terminal and traditional market. This study is expected to be able to help government and stakeholders as a reference in assembling the area around Padalarang railway station.